Experiential Features of Culinary Nutrition Education That Drive Behavior Change: Frameworks for Research and Practice. Issue 3 (May 2020) - Fredericks, Lynn; Koch, Pamela A.; Liu, Ao (Alicia); Galitzdorfer, Leah; Costa, Alyssa; Utter, Jennifer
Evidence of the benefits of culinary nutrition education is growing in the literature. Culinary nutrition education programs are naturally experiential, social, skills-based, and effective in improving nutrition-related beliefs, knowledge, and behaviors. In this article, we explore a set of motivational experiences in culinary nutrition education that have been identified as "drivers" of behavior change. These drivers emerged from 20 years of implementation and evaluation of hands-on cooking programs across the life span in more than 30 states within the United States. From these drivers, we developed a framework to guide both new and existing programs that can be best designed to motivate behavior change. These frameworks add value to the work of culinary nutrition educators and will inform and support future culinary nutrition education programs. In future research, health educators implementing skills-based health promotion programs in diverse settings can test the application of this framework to determine its relevance in broader areas.